Target মাধ্যমিক 2025
\((a^2-bc)x^2+2(b^2-ca)x+(c^2-ab)=0\) বীজদ্বয় সমান হলে দেখাও যে \(b=0\) অথবা, \(a^3+b^3+c^3=3abc\)

সমীকরনের বীজদ্বয় সমান
অর্থাৎ, নিরূপক \(=0\)

\(\{2(b^2-ca)\}^2-4(a^2-bc)(c^2-ab)=0\)
বা, \(4(b^2-ca)^2-4(a^2-bc)(c^2-ab)=0\)
বা, \((b^2-ca)^2-(a^2-bc)(c^2-ab)=0\)
বা, \(b^4-2ab^2c+c^2a^2-(a^2c^2-a^3b\)

\(-bc^3+ab^2c)=0\)



বা, \(b^4-2ab^2c+\cancel{c^2a^2}-\cancel{a^2c^2}+a^3b\)

\(+bc^3-ab^2c)=0\)



বা, \(a^3b+b^4+bc^3-3ab^2c=0\)
বা, \(b(a^3+b^3+c^3-3abc)=0\)

\(\therefore\) হয় \(b=0\)
নয়, \(a^3+b^3+c^3-3abc=0\)
বা, \(a^3+b^3+c^3=3abc\) [প্রমাণিত]
Ganitsarani.in